Fundamentalisme sebagai Ideologi Transisi - Idrus, Muhammad (Unisia, 2016)
This article explores the fundamentalism as a transition ideology. Actually religion is not only covers the doctrine the relationship between God and man, but it also gives the contribution to solve the critical problem of human being such as social, politic, culture problem in accordance with the substance of humanity. Because of the universality of religion that mentioned above, that is the ideal function of religion. In fact, the recent accidents in human life for instance, modernity and the tragedy of World Trade Center September, 11, 2001 indicate that religion (Islam) does not coincide with peace horizon, so Islam is regarded as a religion of fundamentalism. According to writer that fundamentalism is a kind of self defense mechanism of the communities of religion, particularly the community of Muslim how to face the problem of politic, culture, social life etc. It will and always present inhuman history, but the term that refers to it depending on who gives the name to them.